2020
DOI: 10.1002/bbb.2105
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic analysis of inulooligosaccharides, protein, and biofuel co‐production from Jerusalem artichoke tubers: A biorefinery approach

Abstract: Jerusalem artichoke (JA) is a crop with excellent potential for application in biorefineries. It can resist drought, pests, and diseases and can thrive well in marginal lands with little fertilizer application. The JA tubers contain considerable quantities of inulin, which is suitable for the production of inulooligosaccharides (IOS), as a high‐value prebiotic, dietary fiber. In this study, five JA tuber biorefinery scenarios were simulated in Aspen Plus® and further evaluated by techno‐economic and sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The non-random two-liquid (NRTL), electrolyte nonrandom two-liquid (ELECTNRTL) and Peng-Robinson (PENG-ROB) property methods were chosen in the Aspen Plus simulations, based on previous examples of sugarcane biorefineries. 1,[14][15][16] The chemical composition of sugarcane was selected as reported by Dogbe et al, 1 and the component properties in Aspen Plus were taken from Humbird et al 17 The process flowsheets for each scenario can be found in the Supporting Information.…”
Section: Simulation Developmentmentioning
confidence: 99%
“…The non-random two-liquid (NRTL), electrolyte nonrandom two-liquid (ELECTNRTL) and Peng-Robinson (PENG-ROB) property methods were chosen in the Aspen Plus simulations, based on previous examples of sugarcane biorefineries. 1,[14][15][16] The chemical composition of sugarcane was selected as reported by Dogbe et al, 1 and the component properties in Aspen Plus were taken from Humbird et al 17 The process flowsheets for each scenario can be found in the Supporting Information.…”
Section: Simulation Developmentmentioning
confidence: 99%
“…The biorefinery concept focuses on the sustainable conversion of renewable biomasses into a broad range of industrial products, materials, and energy. Inulin-rich biomasses represent inexpensive, renewable, and abundant feedstock to build up a biorefinery strategy ( Li et al, 2013 ; Hughes et al, 2017 ; Bedzo et al, 2020 ). Inulin is a linear polysaccharide (ß-2,1-linked d-fructose residues terminated by a glucose residue) accumulated as a storage carbohydrate in plants such as chicory and dahlia and, more interestingly, in low-requirement crops, such as Jerusalem artichoke and Cynara cardunculus ( Hughes et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of JA are, among others, its ability to grow in poor soil, resistance to pests and common plant diseases and growing much better (in comparison to other energy crops) under salt stress and low temperatures [32,33]. JA tubers are an excellent source of biomass for biofuels and biochemicals manufacturing and have been investigated for ethanol fermentation [34][35][36][37][38][39][40][41], but the use of JA stems as a lignocellulosic feedstock for biofuels and biochemicals is still poorly understood [42].…”
mentioning
confidence: 99%